2023
DOI: 10.1007/s41471-023-00155-1
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of ESG Ratings On Idiosyncratic Stock Risk: The Unrated, the Good, the Bad, and the Sinners

Abstract: This study analyzes whether stocks of companies with environmental social governance (ESG) rating show lower idiosyncratic risk. The main analysis covers 898,757 company-month observations of US stocks in the period from 1991 to 2018 and controls for stocks’ exposure to liquidity, mispricing, innovations in volatility risk, investor sentiment, and analysts’ forecast divergence. The main finding is that the receipt of an ESG rating decreases idiosyncratic stock risk. The effect is stronger for stocks that recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…ESG behaviour and ESG disclosure can reduce the perceived riskiness of companies and hence the cost of capital. According to Horn (2023), ESG ratings reduce idiosyncratic risks and Giese et al (2019) further find that ESG information also reduces systematic risk. Further, Bax et al (2023) find that ESG risks are found to contribute to tail risks in portfolio construction.…”
Section: Introductionmentioning
confidence: 99%
“…ESG behaviour and ESG disclosure can reduce the perceived riskiness of companies and hence the cost of capital. According to Horn (2023), ESG ratings reduce idiosyncratic risks and Giese et al (2019) further find that ESG information also reduces systematic risk. Further, Bax et al (2023) find that ESG risks are found to contribute to tail risks in portfolio construction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Horn and Glück have demonstrated that companies with good ESG performance, which are rewarded with rating upgrades, can effectively diminish downside risk, systematic risk, and idiosyncratic risk [26,27]. Nevertheless, the successful adoption of ESG necessitates gradual modifications and execution, including the elimination of greenwashing and the cessation of regulatory practises.…”
Section: Discussionmentioning
confidence: 99%
“…See also Section 3.4.5. 97 See Oehler et al (2016e), Wendt et al (2018), Horn andOehler et al (2022a). 98 See Oehler et al ( ), (2017d.…”
Section: Deviation From Fully Rational Investorsmentioning
confidence: 99%
“…400 See, inter alia, Oehler et al (2011b), (2012a), ( 2014b), (2018e), and . In this regard, see also the literature assessing sin stocks (see Fabozzi 2017, Fabozzi et al 2008) and literature assessing environmental, social, and governance (ESG) firm ratings that aim at faciliating sustainability-based investment decisions (see Horn 2023.…”
Section: Critical Appraisal and Implicationsmentioning
confidence: 99%